Prolonged outbreak of clonal MDR Pseudomonas aeruginosa on an intensive care unit: contaminated sinks and contamination of ultra-filtrate bags as possible route of transmission?. Issue 1 (December 2016) - Salm, Florian; Deja, Maria; Gastmeier, Petra; Kola, Axel; Hansen, Sonja; Behnke, Michael; Gruhl, Désirée; Leistner, Rasmus
Abstract Background We report on an outbreak in a surgical, interdisciplinary intensive care unit (ICU) of a tertiary care hospital. We detected a cluster of ICU patients colonized or infected with multidrug-resistantPseudomonas aeruginosa . We established an outbreak investigation team, performed an exploratory epidemiological analysis and initiated an epidemiology-based intervention. Methods As part of the outbreak investigation, we performed microbiological examinations of the sinks in the patient rooms and a retrospective case-control study. All patients admitted to the outbreak ICU between January 2012 and February 2014 were included. Cases were patients colonized with the outbreak strain. Controls were patients with a differentPseudomonas aeruginosa strain. Risk factors were evaluated using multivariable conditional logistic regression analysis. Strain typing was performed using the repetitive element-based polymerase chain reaction (rep-PCR) DiversiLab system. Results The outbreak strain was found in the sinks of five (of 16) patient rooms. Altogether 21 cases and 21 (randomly selected) controls were included. In the univariate analysis, there was no significant difference in baseline data of the patients. In the multivariate analysis, stay in a room with a colonized sink (Odds Ratio[OR] 11.2, p = 0.007) and hemofiltration (OR 21.9, p = 0.020) were independently associated with an elevated risk for colonization or infection by the outbreak strain. In a subsequent evaluation of the work procedures associated with hemofiltration, we found that the ultra-filtrate bags had been on average five times per day emptied in the sinks of the patient rooms and were used multiple for the same patient. We exchanged the traps of the contaminated sinks and eliminated work procedures involving sinks in patient rooms by implementation of single use bags, which are emptied outside patient rooms to reduce splash water at the sinks. In the 20 month follow-up period, the outbreak strain was detected only once, which indicated that the outbreak had been ceased (incidence 0.75% vs. 0.04%, p < 0.001) Furthermore, the incidence ofPseudonomas aeruginosa overall was significantly decreased (2.5% vs. 1.5%, p < 0.001). Conclusion In ICUs, limiting work processes involving sinks results in reduced multidrug-resistantPseudomonas aeruginosa rates. ICUs with high rates ofPseudomonas aeruginosa should consider eliminating work processes that involve sinks and potentially splash water in close proximity to patients. Trial registration All data were surveillance based data which were obtained within the German Law on Protection against Infection ("Infektionsschutzgesetz"). Therefore a trial registration was not required.